The Lords of Lambityeco Political Evolution in the Valley of Oaxaca during the Xoo Phase - Lind, Michael (Mesoamerican Worlds, 2009)
"The definitive volume of this Late Classic site. . . . an important contribution to Oaxaca archaeology and to understanding Monte Alb at its peak and during its demise." Veronica Perez Rodriguez, American Anthropologist